Propuesta de una solución virtualizada utilizando software libre como infraestructura en la red de la Universidad Técnica de Cotopaxi extensión La Maná - Mendoza Zambrano, Mercy Karina (2023)
Software Defined Networks are an opportunity to offer quality services, based on the decoupling of control and data planes, which meet the current demands of telecomunications. This research proposes to satisfy the limitations that were detected in the operation, performance and quality of the service at the Technical University of Cotopaxi Extension La Maná. The quasi-experimental method was used with a qualitative approach and the PPDIOO methodology that contemplates the necessary phases to obtain requirements. The virtualization proposal used free software, simulators and controllers were selected and Mininet was chosen as the network emulator, the Aruba Van SDN controller, through the OpenFlow protocol, VMware Workstation and Mikrotik were used as virtualization and communication technology tools. As a result, management is achieved, data monitoring in the designed network and its proper functioning is verified, offering multiple options for direct and centralized management of the network at a high level and the development of applications or APIs for personalized management that offers information or allows changes in real time of the behavior of the network.